ANALISIS EFISIENSI TEKNIS USAHATANI PADI SAWAH TADAH HUJAN DI KABUPATEN BANYUMAS - Rifki Andi Novia; Ratna Satriani (MEDIAGRO, 2020)
ABSTRACT Rainfed lowland rice farming is highly contributed to national rice production after irrigated lowland rice farming. Production of rainfed lowland rice farming faces many obstacles such as cultivation technology and weather changes, inefficient use of production factors as well. This study aimed to analyze the factors influenced the production of rainfed lowland rice farming, the level of technical efficiency and the factors influenced the technical efficiency of rainfed lowland rice farming in Banyumas Regency. The study was conducted in 2 sub-districts in Banyumas Regency for 50 respondentsand was conducted in Planting Season II in 2018. The results showed that the factors affecting the production of rainfed lowland rice farming were the number of seeds, the amount of fertilizer, the amount of pesticides used and arable land area. The level of technical efficiency of rice farming from high level to low level ranged from 0.61 to 0.80 (40 percent); 0.81 - 1.00 (26 percent); less than 0.60 (34 percent) respectively. The result showed that rainfed lowland rice farming in Banyumas Regency was not technically yet efficient and can still be optimized in the use of production inputs to get maximum production results. This study also found that the age variable of farmers significantly affected the inefficiency of rainfed lowland rice farming in Banyumas Regency with a negative regression coefficient. Keywords: efficiency, farming, rainfed lowland, stochastic frontier